Synthesis of Alkyl Aryl Ethers by O-Arylation of Alcohols with Diaryliodonium Salts: Scope, Limitations, and Mechanism - Gallagher, Rory T.; Jha, Soocheta; Metze, Bryan E.; Stuart, David R. (Synlett, 2023)
We describe the development of a C–O coupling reaction between aryl(2,4,6-trimethoxyphenyl)iodonium salts and aliphatic alcohols under weak base conditions. The scope of the reaction is presented, with 16 examples ranging in yield from moderate to high (54–96%). The limitations of the reaction are also presented. Mechanistic experiments reveal a complex network of reactions that include side reactions that generate arynes and oxidize the alcohol nucleophile.
Keywords: arylation; ethers; alcohols; diaryliodonium compounds; ligand coupling; C–O coupling